Pengaruh rekrutmen SDM, penempatan dan komitmen kerja terhadap kinerja karyawan PT LT di Jakarta - Sakti, Sri Handoko; Ikhsan, Muhammad; Abdoellah, M. Natser; Zabidi, Imron; Anggara, Ari (Jurnal Riset Manajemen dan Bisnis, 2023)
Effective human resource management is essential for the success of any organization, particularly in the face of fierce competition. In order to improve overall performance, companies must ensure that their employees are selected and placed in appropriate positions. This study aims to investigate the impact of HR recruitment, placement, and work commitment on employee performance at PT LT. The chosen method was a survey approach, utilizing a quantitative causal associative questionnaire. The results of the regression analysis revealed that HR recruitment, placement, and work commitment all have a significant effect on employee performance. Therefore, it is important for organizations to gain a deeper understanding of how recruitment, placement, commitment, and performance are interconnected in order to maximize their human resources potential and gain a competitive advantage in the market.